Looking for a simplified approach for the propagation of systematic uncertainty in the motion response of a floater. Issue 1 (1st November 2022) - Gueydon, S.; Lyden, E.; Judge, F.; O'Shea, M.; Murphy, J.
Abstract : This new research considers the 3 main motions of the moored floater (surge, heave and pitch) in head waves and it explores ways to estimate the systematic uncertainties on the RAOs, and 2 other metrics for these signals. Based on linear hydrostatics and the linear potential flow theory, simple relations can be found that bind the main characteristics of a floater. These relations are transformed using linear algebra to express how uncertainty bias on the main characteristics of the tested system can be propagated to the motion responses of the floater. Thanks to this approach, variations of the mooring stiffness, position of the centre of mass, radia of gyration can be represented through simple formulations that allow to very effectively assess their impact of the motion RAOs and other metrics. This approach is verified by comparing simulation and test results of the semisubmersible of the MARINET2 floating wind round robin campaign to approximations deduced from these theoretical relations.